From directive to practice: are pictorial warnings and plain packaging effective to reduce the tobacco addiction?. Issue 12 (December 2015) - Mannocci, Alice; Colamesta, Vittoria; Mipatrini, Daniele; Messina, Gabriele; Gualano, Maria Rosaria; Gianfagna, Francesco; Boccia, G.; Langiano, Elisa; Nicolotti, Nicola; Veronesi, Giovanni; Siliquini, Roberta; De Vito, Elisabetta; et al.
Abstract: Objectives: Tobacco packaging represents an important form of promotion of tobacco products and for this reason plain packaging (PP) can be considered an additional tobacco control measure. In Italy the current tobacco packaging is branded with textual warnings. The study investigated the perception of PP with textual warnings (PPTWs) and pictorial warnings (PPPWs) in Italy. Study design: Cross-sectional. Methods: The study was conducted on adults who were current, never and former smokers. The participants watched out three types of packages (current packaging, PPTWs and PPPWs) and eight pictorial warnings, and indicated which they considered the most effective ones to motivate smoking cessation or reduction and to prevent the onset. Results: 1065 subjects were recruited. The PPPWs were considered the most effective in motivating to quit, reduce and prevent the smoking habits (ranged 83.4%–96.1%) in all tobacco users and age groups (≤40/>40 years) ( P  < 0.005). In general PP does not seem to be very effective in quitting for three-quarters of the smokers and 60% declared that they would have still started smoking with PP. The younger group believed less than the older one that PP gives a motivation to quit (29.4% vs 39.1%, P  = 0.002). The pictures perceived as most effective in communicating the smoking effects were lung cancer and gangrene (about one-third of the sample). Conclusions: The textual warnings on tobacco products are a measure of control now outdated. Countries still using them should consider the idea of replace them with pictorial warnings that seem to be more effective. It is also desirable in the near future that these countries introduce the PPPWs. Highlights: The standardized tobacco packaging with textual message does not deter smokers. The pictograms warning result to increase the awareness of the tobacco health risks. Images with gangrene and lung cancers are the most convincing on the risks to health. The textual warnings on tobacco product should be replaced by pictograms firstly.